THE EFFECTIVENESS OF TEACHING READING USING STUDENTS TEAMS ACHIEVEMENT DIVISIONS (STAD) FOR THE FIRST YEAR OF SMA N 2 SUKOHARJO - SUPRIYADI , DEDY (2011)
This research aims at describing the implementation of teaching reading using STAD in SMA N 2 Sukoharjo and describing the effectiveness of teaching reading using STAD in SMA N 2 Sukoharjo. The data are taken from test and document. To collect the required data the researcher compared the results of pre-test and post-test. After collecting and analyzing the data, the researcher described the result of the research. The result in this research is as follows: 1) the researcher knows that STAD technique consists of five steps namely class presentations, terms, quizzes, individual improvement scores, and team recognition. 2) The students’ scores of post-test are significant higher than pre-test scores. It can be seen from the average score that improve 14.38. In the pre test the highest score is 78 and the lowest score is 12 and the average score is 55. 02. And the result of the post test is the highest score is 86 and the lowest score is 30 and the average score is 69.40 and can reach the purpose or the goal in teaching learning process Finally, the researcher concluded that STAD technique is effective for the first year of senior high school